Issues Faced by Working Mothers in Lahore and the Impact of Job Stress on their Relationship with their Adolescent Children - Asifa Sohail; Afza Imtiaz (UMT Education Review, 2018)
The purpose of this study is to investigate the challenges faced by working mothers as they struggle to fulfill the tasks of parenthood and employment in effective ways and the impact of job stressors on their relationship with their adolescent children. The study is qualitative in nature. Data was collected from twenty mother-adolescent dyads; ten working mother-adolescent dyads and ten stay-at-home mother-adolescent dyads were selected from a school in Lahore. Semi-structured interviews and empirical analysis of documents were employed to collect the data. Qualitative interpretive analysis was used to analyze the data and to explore the adolescent-mother relationship and the associated factors which influence this relationship. The study concluded that there was no difference in intimacy and companionship measure of working and non-working mothers with their adolescent children. However, monitoring appeared to be minor in working mothers. The study is expected to help in creating programs and policies that improve the work-life balance of working mothers and families and foster adolescent adjustment in the society.